Between Passion and Rejection – Attitudes to Farming among Young University Graduates in Rural Areas of Poland - Ilona Matysiak (Wieś i Rolnictwo)
The aim of the article is to analyse the significance of farming and agriculture in the lives of young rural university graduates in Poland. Their educational and professional choices are discussed. How many of them graduated from agricultural higher education institutions and agricultural disciplines? Do such decisions translate into taking up farming after having completed the studies? What are the reasons that young people with higher education living in rural areas may be or may not be interested in farming? Another objective is to identify the main factors potentially “pulling” them towards agriculture and those “pushing” them out of this sector. The article is based on 92 in-depth interviews with university graduates aged 25–34 and 27 in-depth interviews with competent local informants conducted in ten purposely selected rural municipalities across Poland. The results show that farming and agriculture are more present in young university graduates than their educational and professional choices suggest. However, the interviews reflect the dominance of the modernisation paradigm shaping the perceptions of farmers and agriculture in Poland.